First person - Scott Collum (The Company of Biologists, 2019)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms (DMM), helping early-career researchers promote themselves alongside their papers. Scott Collum is first author on 'Adenosine and hyaluronan promote lung fibrosis and pulmonary hypertension in combined pulmonary fibrosis and emphysema', published in DMM. Scott is a PhD student in Harry Karmouty-Quintana's lab at the Department of Biochemistry and Molecular Biology, McGovern Medical School, University of Texas Health Science Center at Houston, USA, investigating the molecular mechanisms involved in the initiation and development of chronic lung diseases.